Sharia Business Marketing Strategies in the Era of Economic Digitalization: A Contextual Analysis of Gorontalo City - Nasila, Rahmat; Lamato, B.R. (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Digital transformation has fundamentally reshaped the business landscape, including the Islamic economic sector in Indonesia. This article examines sharia business marketing strategies within the context of economic digitalization, focusing on Gorontalo City. Using a descriptive-qualitative analytical approach, the study identifies that sharia business actors in Gorontalo face dual challenges: limited digital literacy and the need to maintain business practices in accordance with sharia values. The findings indicate that effective digital marketing strategies must integrate sharia principles (honesty, transparency, and fairness) with the utilization of digital platforms that are accessible to local micro, small, and medium enterprises (MSMEs). This article recommends a trust-based digital marketing approach that emphasizes community building, Islamic educational content, and collaboration within the regional sharia business ecosystem.